Amortization of gene replacement therapies: A health policy analysis exploring a mechanism for mitigating budget impact of high-cost treatments. Issue 1 (January 2022) - Dabbous, Monique; Toumi, Mondher; Simoens, Steven; Wasem, Juergen; Saal, Gauri; Wang, Yitong; Osuna, José Luis Huerta; François, Clément; Annemans, Lieven; Graf von der Schulenburg, Johann-Matthias; Sola-Morales, Oriol; Malone, Daniel; et al.
Highlights: Gene replacement therapies (GRTs) are costly, highly valuable therapies. Current constrained healthcare systems are struggling to fund GRTs. Current literature on amortization as a payment model applicable to GRTs is limited. Amortization may be applied to GRTs to mitigate budget impact for payers. Accounting principles and guidelines to date must evolve to apply GRT amortization. Abstract: With gene replacement therapies (GRTs) increasingly and rapidly reaching the healthcare marketplace, the vast potential for improving patient health is matched by the potential budgetary impact for healthcare payers. GRTs are highly valuable given their potential life-extending or even curative benefits and may provide significant cost-offsets compared with standard of care. Current healthcare systems are, however, struggling to fund such valuable but costly therapies. Some payers have already implemented specific financing models to account for the new treatment paradigms, but these do not address the budget impact in the year of acquisition or administration of these costly technologies. This health policy analysis aimed to assess the rationale and feasibility of amortization, within the context of financing healthcare technologies, and specifically GRTs. Amortization is an accounting concept applied to intangible assets that allows for spreading the cost an intangible asset over time, allowing for repayment to occur via interest and principal payments sufficient to repay the intangible asset in full by its maturity. Our systematic scoping review on the amortization of healthcare technologies found a very small literature base with even that being unclear and inconsistent in its understanding of the issues. Where amortization was proposed as a solution for funding costly, but highly valuable GRTs, the concept was not fully investigated in detail, nor was the feasibility of the approach fully challenged. However, by providing clear definitions of relevant concepts along with an example of amortization models applied to some example GRTs, we propose that amortization can offer a promising method for funding of extraordinarily high-value healthcare technologies, thereby increasing market and patient access for these technologies. Nonetheless, healthcare accounting principles and financing guidelines must evolve to apply amortization to the rapidly developing GRTs.